Postoperative leaks in esophagectomy and sleeve gastrectomy for obesity - Rifat Latifi; Agron Dogjani (Albanian Journal of Trauma and Emergency Surgery, 2018)
Postsurgical gastro-intestinal or intestinal-intestinal anastomotic leaks while not frequent, are the most feared complications for any anastomoses performed in the gastrointestinal tract (GIT) by general surgeons. This is particularly important in the upper GIT, such as gastro esophageal anastomosis, where leaks can lead to severe sepsis and septic shock, need for re-operation, or stent placement. For this short review we will address post- operative leaks following esophagectomy and sleeve gastrectomy as the most frequent bariatric procedure today. The factors and causes responsible for Upper Gastro-Intestinal Anastomosis, as they relate to patient, surgeon or technique will be reviewed. Moreover, the diagnosis and current management will be examined.